Families Visit the Museum: A Study on Family Interactions and Conversations at the Museum of the Universe – Rio de Janeiro (Brazil) - Massarani, Luisa; Norberto Rocha, Jessica; Scalfi, Graziele; Silveira, Yan; Cruz, Wailã; Lage dos Santos Guedes, Leandro (Frontiers in Education, 2021)
In this quantitative and qualitative study, we present our analysis on the interactions and conversations of ten families during a visit to the Museum of the Universe, at the Planetarium Foundation of the City of Rio de Janeiro (Brazil). The study of conversations provides a considerable opportunity to address gaps in our current understanding on how families interact and learn in museum environments. The visits were recorded using a subjective camera, and the audiovisual material was analyzed based on a research protocol that combines theoretical and empirical aspects of the visitors’ museum experience. We identified that most of the interactions during the visit occurred between family members and between them and the exhibition, through interactive activities and moments of contemplation. Parents/caregivers played an important role in maximizing the children's learning opportunities as they interacted and talked about the exhibits. The conversations were related to science topics, especially astronomy, as well as aspects on how to operate the exhibition modules. The results suggest that the Museum of the Universe has become a platform for families to share experiences, discuss and develop specific ideas, knowledge and concepts about astronomy, enriching the group members’ awareness.